2020
DOI: 10.2196/17129
|View full text |Cite
|
Sign up to set email alerts
|

Paper Versus Digital Data Collection Methods for Road Safety Observations: Comparative Efficiency Analysis of Cost, Timeliness, Reliability, and Results

Abstract: Background Roadside observational studies play a fundamental role in designing evidence-informed strategies to address the pressing global health problem of road traffic injuries. Paper-based data collection has been the standard method for such studies, although digital methods are gaining popularity in all types of primary data collection. Objective This study aims to understand the reliability, productivity, and efficiency of paper vs digital data co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Other registries have undergone the development from paper to electronic records similar to the DCAR has with the same success 16,17 In 2016 the validation of data became more substantial and additional variables were added. Survival after 30 days has increased throughout the years along with the rising incidence of OHCA, and in 2018, the 30-day survival following OHCA was 16%.…”
Section: Discussionmentioning
confidence: 99%
“…Other registries have undergone the development from paper to electronic records similar to the DCAR has with the same success 16,17 In 2016 the validation of data became more substantial and additional variables were added. Survival after 30 days has increased throughout the years along with the rising incidence of OHCA, and in 2018, the 30-day survival following OHCA was 16%.…”
Section: Discussionmentioning
confidence: 99%
“…14 Online surveys have the advantages of being a quick and economic response instrument, with a wide geographical reach, which may increase the feasibility of health-related studies. 14,16,47,48 Thus, in a 10-year prospective cohort study, it has been found that the web-based version of data collection does not imply a loss in data quality. 49 Furthermore, the webbased questionnaires were completed to a greater extent and with less missing data than paper-based ones.…”
Section: Discussionmentioning
confidence: 99%
“…78,79 Comparison with prior work One of the biggest difficulties concerning these analyses was finding comparable studies. Most web-based studies available are based on dietary and physical activity interventions for weight loss primarily, [80][81][82] Literature shows articles comparing web-based with non-web-based, 13,47,49 physical, 15 telephone, mailing 83 or postal 14 data collection. Other study compared the characteristics of a sample of pregnant smokers, recruited through four different online platforms (three crowdsourcing platforms and one social media site) and describes the differences and feasibility of each platform as well as the costs per completed survey.…”
Section: Limitations and Strengthsmentioning
confidence: 99%
“…Taber et al for instance support this point and note that although the fixed costs for DDC were higher, the variable costs were much lower than for PBDC, resulting in a 7.73% lower overall cost. 28 Njuguna et al also indicate in their study on the cost-effectiveness of digital-based applications that during their establishment, the cost of DDCs was 9.4% higher than that of PPDC. However, after 2 years, DDC costs decreased by 7%, compared with PPDC.…”
Section: Bmj Global Healthmentioning
confidence: 97%